Pore scale investigation of hydrogen injection in sandstone via X-ray micro-tomography. (11th October 2021) - Jha, Nilesh Kumar; Al-Yaseri, Ahmed; Ghasemi, Mohsen; Al-Bayati, Duraid; Lebedev, Maxim; Sarmadivaleh, Mohammad
Abstract: The challenge associated with large-scale hydrogen storage is a pertinent one to achieve a hydrogen economy. The increasing global demand for clean and green energy is the driving force to propel such an economy. Furthermore, hydrogen is also considered an alternative energy source compared to fossil fuel as a clean energy alternative. Hydrogen geo-storage in a deep saline aquifer, depleted oil and gas reservoirs can resolve this challenge. We assess the potential of a saline aquifer in a sandstone formation to store hydrogen through first-of-its-kind x-ray micro-computed tomography miniature coreflood experiments. The investigation shows that 65% of the sandstone's pore volume can be occupied by hydrogen when injected at a slow rate. Residual saturation of hydrogen upon brine injection can be 41%. Graphical abstract: Image 1 Highlights: A large-scale hydrogen geo-storage is under assessment in sub-surface formations. Initial and residual saturations are 65% and 41%, respectively, for sandstone. Wettability of hydrogen/brine/rock system is favourable for hydrogen geo-storage.